Long-Term Monitoring of Wrong-Way Maneuvers at Diverging Diamond Interchanges. Issue 1 (January 2015) - Vaughan, Christopher; Jagadish, Chaithra; Bharadwaj, Shreyas; Cunningham, Christopher M.; Schroeder, Bastian J.; Hummer, Joseph E.; Findley, Daniel; Rouphail, Nagui M.
With the popularity of diverging diamond interchanges (DDIs), also called double crossover diamonds, on the rise, there has been a growing concern about the potential for wrong-way maneuvers. With the mainline crossover configuration at this interchange, the risk of vehicles traveling down the wrong direction is one of the most vital and feared public safety concerns at DDIs. This concern is especially important as DDIs are being installed at a rapid pace across the country. As part of an ongoing FHWA research project, a team of researchers was tasked with continuously monitoring five DDIs for 6 months to observe rates and causes of wrong-way maneuvers. The team installed video cameras at each of the DDIs and postprocessed the video by using video detection software; this procedure results in a more efficient method of monitoring the crossovers at these DDIs. The software polls generated by the detection software were manually verified by analysts after the video was processed, and the findings are presented in this paper. The analysis showed that wrong-way maneuvers tended to occur more often when vehicles were first entering the DDI rather than after correctly moving through the first crossover and going the wrong way at the second crossover that they approached (traveling outbound). Likewise, wrong-way maneuvers were found to occur more frequently at night than during the day. The findings show that DDIs do experience a certain level of wrong-way maneuvers; however, no crashes could be identified from safety records that were associated with these events. Consequently, DDIs have generally proved to be safe and efficient movers of traffic when designed appropriately.